Peran Csr Pt.Astra International Tbk Dalam Pemberdayaan Ekonomi Masyarakat (Umkm) Melalui Kampung Berseri Astra - Yuli Ermawati; Puijianto Puijianto; Rodhiah Rodhiah (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia, which are contributors to national economic growth, still experience many obstacles in their development, such as ineffective partnership patterns, and their development does not meet expectations. This makes the implementation of CSR carried out by companies or BUMN still not on target or still partial. The aim of this research is to evaluate and create a pattern of synergy between the implementation of corporate CSR and community economic empowerment in the form of MSMEs. This research was conducted at PT Astra International Tbk with one of the CSR partners in the form of Kampung Berseri Astra, namely KBA Semanggi Suroboyo. The research method is a qualitative approach, using 3 key informants. The results of the research show that PT Astra International Tbk has committed to implementing corporate CSR with a focus on community economic development through Kampung Berseri Astra which is developed and monitored continuously every year through 4 main pillars, namely Education, Health, Environment and Entrepreneurship. KBA Semanggi Suroboyo, as one of the partners, feels that the implementation of CSR is right on target, but is still hampered by the synergy of regional government programs, especially those related to empowering MSMEs. An appropriate synergy pattern is needed to synergize the implementation of the Company's CSR with community economic empowerment, especially in terms of empowering MSMEs.